Examining the Risk of Potentially Preventable Hospitalization in Adults With Congenital and Acquired Disabilities. (17th December 2021) - Mahmoudi, Elham; Lin, Paul; Khan, Anam; Kamdar, Neil
Abstract: Introduction: Adults with congenital (cerebral palsy/spina bifida (CP/SB)) or acquired disabilities (spinal cord injury (SCI) or multiple sclerosis (MS)) are more likely than those without disability to develop medical complications. Little is known about potentially preventable hospitalizations (PPH) among adults with disabilities. PPHs are preventable if a patient had timely access to care. Our objective was to estimate PPH risk for each of the aforementioned disabilities. Methods: We used private payer claims data from 2007-2017 to identify adults (18+) with diagnoses of CP/SB (n=10, 617), SCI (n=5, 173), and MS (n=6, 198). Adults without these disabilities were included as controls. We propensity score matched individuals for age and sex. Logistic regression models with repeated measures were subsequently applied, adjusting for age, sex, race/ethnicity, health indicators, U.S. census divisions, and socioeconomic variables. Odd ratios (OR) were compared over 4-years of follow up. Results: Adults with CP/SB, SCI, and MS had higher odds of any PPH compared with adults without disability [CP/SB: (OR=4.10; 95% CI: 2.31-7.31); SCI: (OR=1.67; 95% CI: 1.21-2.32); and MS: (OR=1.48; 95% CI: 1.00-2.25)]. Use of preventative services reduced the PPH risk. For example, wellness visit reduced the odds of PPH by almost half [CP/SB: (OR=0.52; 95% CI: 0.41-0.67); SCI: (OR=0.57; 95% CI: 0.45-0.71); and MS: (OR=0.53; 95% CI: 0.40-0.66)]. Conclusions: Adults with disabilities are at greater odds of PPH compared to adults without disabilities. Clinical guidelines for use of preventative care for adults living with disabilities need to be accordingly updated.